Study on the thermal storage properties of a spiral tube heat storage tank based on numerical analysis - Yuna, Li; Xiaojun, Wang; Yu, Yang; Tao, Wang (Frontiers in Energy Research, 2024)
Introduction The spiral tube heat storage tank is a highly efficient device designed for storing and releasing heat, utilizing a spiral tube structure. Its key advantages include efficiency, reliability, and flexibility, making it suitable for a wide range of conditions, from high temperatures and pressures to low temperatures and high vacuums. Methods This study aims to analyze phase change heat storage in spiral tube heat storage tanks using numerical simulation. Results It explores the impact of varying water supply temperatures on heat transfer efficiency and the melting behavior of phase change materials within the tanks. Proposed enhancements, informed by numerical simulation results, seek to improve heat transfer efficiency. Simulation findings indicate that charging efficiency rises with increased temperature differentials, akin to sleeve-type heat exchangers. Discussion Calculations suggest faster melting of phase change materials at the central position of the tank’s spiral tube, with slower melting near the vessel wall. Consequently, reducing the number of spiral tubes in the middle is suggested for future structural optimization.